ISU-ISU FIQH SEMASA BERKAITAN ZAKAT PERTANIAN DI MALAYSIA: Current Issues Relating to Fiqh in Agricultural Zakah in Malaysia - Ali, Nor Aini; Hj Abdullah, Luqman (Jurnal Syariah, 2013)
In Malaysia, agricultural zakah is levied only on paddy and assessment of agricultural zakah is based on enactment or fatwas in the state. This article will discuss current fiqh issues in agricultural zakah according to the opinions of scholars from different schools of laws and a study on the related fatwas such as zakah rate, nisab, method of assessment, zakah on paddy subsidy and the payment of zakah. This article uses the library research method to collect data and content analysis to analyse the data. The main finding shows that the assessment of nisab of agricultural zakah (such as tonne and kilogram) needs to be done in accordance with the current price of paddy (Ringgit Malaysia). The finding also established that there are some contemporary scholars who allow deductions of the production cost of agriculture dan cost of living in the assessment of agricultural zakah. Third, fatwas in Malaysia have shifted from fully dependant on Shafi’i school of law to other schools of law and even to the views of contemporary scholars in issues related to agricultural zakah.